Jitegemee (rely on yourself): a cross-sectional study on acceptability, feasibility and design considerations for a personal savings intervention to reduce HIV risk among female sex workers in Siaya County, Kenya - Harsha Thirumurthy; Kawango Agot; Nicky Okeyo; Jacob Onyango; Marylyn Ochillo; Gift-Noelle Wango; Moraa Arasa; Timothy Okello; Olivia Okumu; Shantana Carol; Bernard Ayieko (BMJ Open)
Objectives The primary objective was to assess the acceptability of a savings intervention in which female sex workers (FSW) would save part of their earnings and call back (withdraw) when faced with a financial need that could force them into HIV risk practices. The secondary objectives were to assess its feasibility, concerns and design considerations.Design A cross-sectional survey. Participants were asked for views on the intervention, their earnings, saving and spending practices, and suggestions for the intervention package.Setting Kisumu and Siaya counties, Kenya.Participants FSWs aged ≥18 years, self-identifying as sex workers and living in Kisumu or Siaya county.Outcome measures The primary outcome was the proportion of participants who believed the Jitegemee intervention would be acceptable to FSWs in Kenya. The secondary outcomes were the proportion who: could generate money to save (assessed from income, spending and loaning practices), reported potential challenges with the intervention and suggested components to inform the intervention package.Results We enrolled 369 FSWs, 88% aged 18–39 years, 78% unmarried, 94% cared for ≥1 child(ren) and 78% were household heads. Over half (52.1%) had been in sex trade for ≤4 years, with 62.3% reporting <10 clients the previous month. Jitegemee was highly acceptable, at 94.8%; however, participants suggested adding: financial literacy, including saving, spending and loans management (74.8%), forming saving groups (37.5%) and goal-setting (24.1%). Those who did not care for children were 4.86 times more likely to save (adjusted OR (aOR)=4.86, p=0.18), non-household heads were less likely to save (aOR=0.57, p=0.28) and those in the sex trade for 1–4 years and 5–9 years were four to five times more likely to save than those <1 year (aOR=4.49, p=0.01 and aOR=5.22, p=0.01, respectively).Conclusions Jitegemee intervention was highly acceptable; however, several recommendations were suggested to make the design more appealing and potentially effective.